ENCOUNTER “THE DISAPPEARANCE OF CHILDREN” TROUGH SCHOOL LITERACY MOVEMENT - Ahmad Iklil Saifulloh, Hajar Nurma Wachidah (LEMBAGA PENELITIAN, PENGABDIAN PADA MASYARAKAT, PENINGKATAN AKTIVITAS INSTRUKSIONAL, PENINGKATAN DAN PENJAMINAN MUTU UNIVERSITAS ISLAM MAJAPAHIT, 2020)
The disappearence of childern be the main major problem face nowdays, mass madia consumtion, games, and adulthood life style always no one in social media such as Youtube and Instagram. Games as new alternative entertainment for childern post Corona Virus 2019 even uncounterable and addicted. In the future, technology becomes a king for other descipline, culture, local wisdom, and many more. We already surrender towards technology.Its Imposible to kill technology, but School Literacy Movement has samall alternate portion to save our future generation. The function uf this movement is to build up our mind to be more critical and ethical. By means of implementation of this movement we are trying to use Qualitative approach with interviews, field observations, and documentation as our Instrument. The rommate area in the Elementary School of Sumber Jati Village was choosen to be our community enggegement. And thre are five result focuses; Reactifating the School Library, Inviting Moving Library from Mojokerto District, Literacy Movement and its guidance from Islamic University of Majapahit and Librarian from Mojokerto, Applicable scientific updates related to models and reading techniques, and Habitual action within 15 minutes to listen a story of local wisdom in Indonesia.